Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $\{f_k\}$ and $\{g_k\}$ be sequences of real numbers. The formula for summation by parts is given by:

$\sum_{k=m} ^n f_k \Delta g_k=(f_{n+1}g_{n+1}-f_mg_m)-\sum_{k=m} ^n g_{k+1}\Delta f_k$,

where $\Delta f_k=f_{k+1}-f_k$.

Letting $f_k=2k+1$ and $g_k=-\frac{1}{k}$. One then computes $\Delta f_k=2$ and $\Delta g_k=\frac{1}{k(k+1)}$. Therefore, using the partial summation formula, we have

\begin{align*} \sum_{k=1} ^n f_k \Delta g_k=\sum_{k=1} ^n \frac{2k+1}{k(k+1)}&=-\frac{2n+3}{n+1}+3+\sum_{k=1} ^n \frac{2}{k+1} \\ &=\frac{n}{n+1}+2(H_n-1)\\ &=2H_n-\frac{n+2}{n+1}, \end{align*}

where $H_n$ denotes the $n^{th}$ harmonic number.

I have check my answer multiple times, but I am convinced it is incorrect. Could anyone point out a flaw in my reasoning?

Here is the full solution:

Let $f_k=2k+1$ and $g_k=-\frac{1}{k}$. One then computes $\Delta f_k=2$ and $\Delta g_k=\frac{1}{k(k+1)}$. Therefore, \begin{align*} \sum_{k=1} ^n f_k \Delta g_k=\sum_{k=1} ^n \frac{2k+1}{k(k+1)}&=-\frac{2n+3}{n+1}+3+\sum_{k=1} ^n \frac{2}{k+1} \\ &=\frac{n}{n+1}+2(H_{n+1}-1)\\ &=2H_n+\frac{n}{n+1}-2\frac{n}{n+1}\\ &=2H_n-\frac{n}{n+1}. \end{align*}

share|cite|improve this question
The answer's supposed to be $2H_n-\dfrac{n}{n+1}$. – J. M. Apr 29 '12 at 15:20
that's exactly what I thought it should be, but I cannot reconcile this with my calculations. – Holdsworth88 Apr 29 '12 at 15:31
Apparently you evaluated your last sum wrong: $$\sum_{k=1}^n \frac1{k+1}=H_n-\frac{n}{n+1}$$ – J. M. Apr 29 '12 at 15:39
up vote 4 down vote accepted

It does look to be your final conversion to harmonic numbers is at fault. In particular,

$$\begin{align*} \sum_{k=1}^n \frac1{k+1}&=\sum_{k-1=1}^n \frac1{k-1+1}\\ &=\sum_{k=2}^{n+1} \frac1{k}\\ &=H_{n+1}-1\\ &=H_n+\frac1{n+1}-1\\ &=H_n-\frac{n}{n+1} \end{align*}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.